2010
DOI: 10.4065/mcp.2010.0103
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Direct Measures of Body Composition and Prognostic Factors in Chronic Heart Failure

Abstract: Objective: To explore the covariate-adjusted associations between body composition (percent body fat and lean body mass) and prognostic factors for mortality in patients with chronic heart failure (CHF) (nutritional status, N-terminal pro-B-type natriuretic peptide [NT-proBNP], quality of life, exercise capacity, and Creactive protein).Patients and MethOds: Between June 2008 and July 2009, we directly measured body composition using dual energy x-ray absorptiometry in 140 patients with systolic and/or diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
5
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 32 publications
3
121
5
6
Order By: Relevance
“…10,12 Body mass index does not detect the total amount of body fat 12,35,36 and its classification does not vary according to sex, age or ethnicity. 36 As well as in cases of heart failure, the obesity paradox has been shown in other cardiovascular disorders such as coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…10,12 Body mass index does not detect the total amount of body fat 12,35,36 and its classification does not vary according to sex, age or ethnicity. 36 As well as in cases of heart failure, the obesity paradox has been shown in other cardiovascular disorders such as coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 The LBM can serve as an index of muscle mass and somatic protein storage, whereas fat mass more directly reflects energy storage. A prospective study in 535 patients receiving HD showed that lower body fat or a decline in body fat percentage over time was associated with an increased risk of death.…”
Section: Gained Muscle Mass Referencementioning
confidence: 99%
“…29 • Body composition: Lean body mass but not body fat was associated with favorable changes in prognostic factors. 30 A decreased BMI could be a surrogate of the "malnutrition-inûammation complex syndrome" that may cause a worse prognosis. 31 • Enlarged muscle mass and better nutritional status: Higher mortality in the low BMI categories may be due to the sarcopenic obesity that is characterized by low muscle mass.…”
Section: Discussionmentioning
confidence: 99%